ANALYSIS OF CAPITAL AND BUSINESS EXPERIENCE IN DETERMINING SHRIMP POND BUSINESS INCOME IN TAMBAKSUMUR VILLAGE FARMERS' GROUP, TIRTAJAYA DISTRICT, KARAWANG - Santi Pertiwi Hari Sandi; Dedi Mulyadi (International Journal of Management, Economic, Business and Accounting, 2025)
Purpose of the study — The purpose of this study is to determine and analyze the capital and business experience owned by shrimp farmers in influencing their income from shrimp farming in Tambak Sumur Village, Tirtajaya District, Karawang. Research method— This study employs a qualitative descriptive method. Data collection was conducted using primary data obtained through direct interviews with shrimp farmers. Result— The study involved a sample of six shrimp farmers. Findings indicate that the business experience of these farmers is primarily derived from their parents' experiences. Notably, high income is achieved during the favorable season from March to June, with average daily sales ranging from 100 kg to 300 kg. Conversely, the period from October to December is marked by significant losses, ranging from 50% to 90%. Conclusion— The capital and business experience of shrimp farmers do not significantly determine their income increase. Instead, income is heavily influenced by factors such as seed quality, maintenance processes, seasonal variations, water quality, feed quality, shrimp yields, and the occurrence of shrimp diseases, including viruses that can lead to mass mortality in shrimp.